Pengaruh Struktur Kepemilikan, Ukuran Komite Audit, Ukuran Dewan Komisaris dan Jenis Kepemilikan Terhadap Manajemen Laba - Alma Nadya Pramitha (Jurnal Akuntansi Bisnis, 2021)
The purpose of this study is to re-examine the determinants of earnings management using companies listed on the Indonesia Stock Exchange. More specifically, this study examines the effect of ownership structure, size of the board of commissioners, and size of the audit committee on earnings management. This research is different from previous research conducted in the Indonesian capital market because it adds a new variable, namely the type of ownership. The sample was taken from the period 2015-2019 with purposive sampling method. A total of 1833 company observations could be collected during the study period. However, 513 observations must be eliminated to meet assumptions underlying multiple regression. The study included three control variables to control for differences in the characteristics of the company sample, namely company size, leverage, and profitability. The results of the regression analysis show that: 1) Institutional ownership has no significant effect on earnings management. 2) Managerial ownership has no significant effect on earnings management. 3) size of Audit Committee has no significant effect on earnings management. 4) Board of Commissioners size has no significant effect on earnings management. 5) Type of Ownership has a significant positive effect on earnings management. In addition, of the three control variables used, there are two that affect earnings management, namely firm size and profitability. Leverage has no significant effect on earnings management.